'It's Not Just about Faith': Narratives of Transformation When Moving Out of Islam in the Netherlands and Britain. Issue 3 (3rd July 2019) - Vliek, Maria
ABSTRACT: This article investigates the narratives of people with Islamic backgrounds in the Netherlands and Britain who have moved out of Islam. Rather than focusing primarily on 'leaving faith' (i.e. a predominantly negative and religiously centred approach), it will present four types of thematic trajectories that consider the broader life-worlds and experiences of the interlocutors. These themes will illustrate the relative weight of the religious voice in trajectories, rather than presupposing the centrality of religion in one's (former) identity or trajectory. It will thereby display a broader understanding of the interlocutors' experiences as being in a negative relation to religion alone: not only religious, but also political, social, ethnic and gender boundaries provided the contexts in which people moved out of Islam. The themes ('religious break', 'social break-away', 'the entrance' and 'unconscious secularization') will be illustrated by four case studies. A fifth case will be presented to illustrate the potency of the intertwinement of the themes.